2014
DOI: 10.1007/s40279-013-0141-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Acceleration at the Onset of Exercise: A Potential Parameter for Monitoring Progress During Physical Training in Sports and Rehabilitation

Abstract: There is a need for easy-to-use methods to assess training progress in sports and rehabilitation research. The present review investigated whether cardiac acceleration at the onset of physical exercise (HRonset) can be used as a monitoring variable. The digital databases of Scopus and PubMed were searched to retrieve studies investigating HRonset. In total 652 studies were retrieved. These articles were then classified as having emphasis on HRonset in a sports or rehabilitation setting, which resulted in 8 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…To better reflect the vagal modulation over cardiac chronotropism, 4sET was based on well-established physiological mechanisms 1 , 5 , 14 , 20 , 21 : a) respiratory-heart interaction: deep and rapid inspiration stimulates afferent pathways, which act on structures in the central nervous system and trigger a rapid increase in vagal activity on the sinus node, resulting in an abrupt decrease in HR, which is typically observed in a few seconds; b) movement-heart interaction: rapid movement of the extremities stimulates afferent pathways that act on the central nervous system, triggering a strong and fast (latency period probably <1 s) inhibition of acetylcholine release in vagal efferent fibers of the sinus node, thereby causing an abrupt increase in HR; c) although the movement of large joints and the contraction of skeletal muscles also promotes sympathetic stimulation, this response has a latency >4 s before cardiac stimulation can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…To better reflect the vagal modulation over cardiac chronotropism, 4sET was based on well-established physiological mechanisms 1 , 5 , 14 , 20 , 21 : a) respiratory-heart interaction: deep and rapid inspiration stimulates afferent pathways, which act on structures in the central nervous system and trigger a rapid increase in vagal activity on the sinus node, resulting in an abrupt decrease in HR, which is typically observed in a few seconds; b) movement-heart interaction: rapid movement of the extremities stimulates afferent pathways that act on the central nervous system, triggering a strong and fast (latency period probably <1 s) inhibition of acetylcholine release in vagal efferent fibers of the sinus node, thereby causing an abrupt increase in HR; c) although the movement of large joints and the contraction of skeletal muscles also promotes sympathetic stimulation, this response has a latency >4 s before cardiac stimulation can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…One can presume that τ RR during provocative testing is mostly controlled by the stress protocol, for instance, by the steepness of exercise intensity variation and duration of exercise stages. However, it has been demonstrated that individual heart rate kinetics to a given stress level are variable among humans (Hettinga et al., ). It remains to be elucidated whether such variability is sufficient to undermine QT‐hys estimates using the aforementioned methods during a fixed stress protocol.…”
Section: Discussionmentioning
confidence: 99%
“…4 Because "athlete" is a quite unspecific label in terms of actual physical fitness (aerobic fitness, flexibility, muscle strength/power, balance and body composition), encompassing subjects with remarkably different physical and physiological profiles, 10 significant controversy exists regarding cardiac autonomic modulation in "athletes". [11][12][13][14][15][16] While some studies describe a tendency to a higher cardiac vagal modulation in athletes, 11,12,[17][18][19] this has at national and international levels, including some FIFA World Cup participants. All participants of the study read and signed an informed consent form and agreed to participate in the evaluation protocol and in having their data used for scientific purposes.…”
Section: Andmentioning
confidence: 99%